QUIZ TEAM LEARNING MODEL ON STUDENT PERFORMANCE IN ISLAMIC RELIGIOUS EDUCATION - Isroani, Farida; Munir, Munir (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
As a factor that influences the effectiveness of learning, the teacher must possess a number of competencies. The mastery of the learning model as a support for the learning process is one of them. The Group Question (Quiz Team) model is one of the learning models that can train students' abilities. The Quiz Team discovered a form of active learning model that functions to train students' activeness to ask and answer each other, so that teachers can create a fun and engaging learning environment so that students are active in class when they are learning. As respondents, eighth graders comprise the sample population. Observation, interviews, tests, documentation, questionnaires, and tests were employed to collect data. The results demonstrated that the implementation of the Quiz Team learning model increased student success in learning.